2011
DOI: 10.1016/j.appet.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Alternative thinking about starting points of obesity. Development of child taste preferences

Abstract: A c c e p t e d M a n u s c r i p t 2 Food marketers are at the epicenter of criticism for the unfolding obesity epidemic as societies consider banning advertising to children and taxing "junk" foods. While marketing's role in obesity is not well understood, there is clear evidence that children are regularly targeted with calorie-dense, nutrient-poor food. Much of the past research seeks to understand how marketing influences brand preference and child requests. The authors argue that understanding palate dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 74 publications
2
34
0
8
Order By: Relevance
“…These results are somewhat concerning, given the research suggesting that exposure to sodium and added sugars in early life can affect taste preferences, intake, and health later in life. [13][14][15]40 Our study is the most recent and comprehensive research on the sodium and sugar content of US commercial infant and toddler food products. Despite differences in thresholds used to identify excess nutrient content, food products, and food categories, our overall findings on sodium and total sugar content are similar to the Canadian studies indicating 25,26 many types of infant and toddler food products did not have low sugar or sodium content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are somewhat concerning, given the research suggesting that exposure to sodium and added sugars in early life can affect taste preferences, intake, and health later in life. [13][14][15]40 Our study is the most recent and comprehensive research on the sodium and sugar content of US commercial infant and toddler food products. Despite differences in thresholds used to identify excess nutrient content, food products, and food categories, our overall findings on sodium and total sugar content are similar to the Canadian studies indicating 25,26 many types of infant and toddler food products did not have low sugar or sodium content.…”
Section: Discussionmentioning
confidence: 99%
“…Early life exposures to sodium and sugar can set taste preferences and determine health trajectories. [13][14][15] Furthermore, the majority of US children visit pediatricians annually, thus providing opportunities for counseling parents about food choices for their children. 16 According to the 2014 American Academy of Pediatrics Nutrition Handbook, "food choices to be encouraged, whether home or commercially prepared, are those with no added salt or sugar."…”
Section: What This Study Addsmentioning
confidence: 99%
“…3 Sensory attributes of foods, especially food hedonics, are known to have an important role in human eating behaviour 4,5 and may thus have some responsibility in the obesity epidemic. [6][7][8][9] Although this question is of interest to better define public health actions, it remains unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of British parents, researchers found correlations between children's attempts to influence their parent's purchases and the type of product, with the strongest correlations for sweets, snack foods and cereals (21) . Given children's preference for both high-sugar and high-fat foods (22,23) , and the powerful forces of marketing such items to children, it is plausible that frequent compliance with children's food requests could result in unhealthy diets. However, the effect of pestering on health outcomes is unknown.…”
mentioning
confidence: 99%